Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2024) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Stuart G. Siddell; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Bas E. Dutilh; Juliana Freitas-Astúa; María Laura García; et al. (Archives of Virology, 2024)
This article reports changes to virus taxonomy and taxon nomenclature that were approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2024. The entire ICTV membership was invited to vote on 203 taxonomic proposals that had been approved by the ICTV Executive Committee (EC) in July 2023 at the 55th EC meeting in Jena, Germany, or in the second EC vote in November 2023. All proposals were ratified by online vote. Taxonomic additions include one new phylum ( Ambiviricota ), one new class, nine new orders, three new suborders, 51 new families, 18 new subfamilies, 820 new genera, and 3547 new species (excluding taxa that have been abolished). Proposals to complete the process of species name replacement to the binomial (genus + species epithet) format were ratified. Currently, a total of 14,690 virus species have been established.

Ozone at Mace Head, Ireland from 1987 to 2021: Declining baselines, phase-out of European regional pollution, COVID-19 impacts - Richard G. Derwent; David D. Parrish; Alistair J. Manning; T. Gerard Spain; Peter G. Simmonds; Simon O'Doherty (Atmospheric Environment, 2024)

High-frequency, continuous hydrogen observations at Mace Head, Ireland from 1994 to 2022: Baselines, pollution events and ‘missing’ sources - Richard G. Derwent; Peter G. Simmonds; Simon O'Doherty; Alistair J. Manning; T. Gerard Spain (Atmospheric Environment, 2023)

Correction to: Changes to virus taxonomy and the ICTV Statutes ratifed by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Renaming of the genus Flavivirus to Orthoflavivirus and extension of binomial species names within the family Flaviviridae - Thomas S. Postler; Martin Beer; Bradley J. Blitvich; Jens Bukh; Xavier de Lamballerie; J. Felix Drexler; Allison Imrie; Amit Kapoor; Galina G. Karganova; Philippe Lemey; Volker Lohmann; Peter Simmonds; et al. (Archives of Virology, 2023)

Seasonal dynamics of the wild rodent faecal virome - Jayna Raghwani; Christina L. Faust; Sarah François; Dung Nguyen; Kirsty Marsh; Aura Raulo; Sarah C. Hill; Kris V. Parag; Peter Simmonds; Sarah C. L. Knowles; Oliver G. Pybus (Molecular Ecology, 2023)
Viral discovery studies in wild animals often rely on cross‐sectional surveys at a single time point. As a result, our understanding of the temporal stability of wild animal viromes remains poorly resolved. While studies of single host–virus systems indicate that host and environmental factors influence seasonal virus transmission dynamics, comparable insights for whole viral communities in multiple hosts are lacking. Utilizing noninvasive faecal samples from a long‐term wild rodent study, we characterized viral communities of three common European rodent species ( Apodemus sylvaticus , A. flavicollis and Myodes glareolus ) living in temperate woodland over a single year. Our findings indicate that a substantial fraction of the rodent virome is seasonally transient and associated with vertebrate or bacteria hosts. Further analyses of one of the most common virus families, Picornaviridae, show pronounced temporal changes in viral richness and evenness, which were associated with concurrent and up to ~3‐month lags in host density, ambient temperature, rainfall and humidity, suggesting complex feedbacks from the host and environmental factors on virus transmission and shedding in seasonal habitats. Overall, this study emphasizes the importance of understanding the seasonal dynamics of wild animal viromes in order to better predict and mitigate zoonotic risks.

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Recent changes to virus taxonomy ratified by the International Committee on Taxonomy of Viruses (2022) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2022)

Differentiating between viruses and virus species by writing their names correctly - Francisco Murilo Zerbini; Stuart G. Siddell; Arcady R. Mushegian; Peter J. Walker; Elliot J. Lefkowitz; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Bas E. Dutilh; María Laura García; Sandra Junglen; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Andrew J. Davison; Donald M. Dempsey; Bas E. Dutilh; María Laura García; Balázs Harrach; Robert L. Harrison; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Changes to virus taxonomy and the Statutes ratified by the International Committee on Taxonomy of Viruses (2020) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Donald M. Dempsey; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; R. Curtis Hendrickson; Sandra Junglen; Nick J. Knowles; et al. (Archives of Virology, 2020)

Correction to: Binomial nomenclature for virus species: a consultation - Stuart G. Siddell; Peter J. Walker; Elliot J. Lefkowitz; Arcady R. Mushegian; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2020)
The article Binomial nomenclature for virus species: a consultation, written by Stuart G. Siddell, Peter J. Walker, Elliot J. Lefkowitz, Arcady R. Mushegian, Bas E. Dutilh.

Binomial nomenclature for virus species: a consultation - Stuart G. Siddell; Peter J. Walker; Elliot J. Lefkowitz; Arcady R. Mushegian; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2020)
The Executive Committee of the International Committee on Taxonomy of Viruses (ICTV) recognizes the need for a standardized nomenclature for virus species. This article sets out the case for establishing a binomial nomenclature and presents the advantages and disadvantages of different naming formats. The Executive Committee understands that adopting a binomial system would have major practical consequences, and invites comments from the virology community before making any decisions to change the existing nomenclature. The Executive Committee will take account of these comments in deciding whether to approve a standardized binomial system at its next meeting in October 2020. Note that this system would relate only to the formal names of virus species and not to the names of viruses.

Changes to virus taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2019) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Donald M. Dempsey; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; R. Curtis Hendrickson; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Additional changes to taxonomy ratified in a special vote by the International Committee on Taxonomy of Viruses (October 2018) - Stuart G. Siddell; Peter J. Walker; Elliot J. Lefkowitz; Arcady R. Mushegian; Michael J. Adams; Bas E. Dutilh; Alexander E. Gorbalenya; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; et al. (Archives of Virology, 2019)

Changes to taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2018) - Andrew M. Q. King; Elliot J. Lefkowitz; Arcady R. Mushegian; Michael J. Adams; Bas E. Dutilh; Alexander E. Gorbalenya; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; et al. (Archives of Virology, 2018)

Changes to taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2017) - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2017)

50 years of the International Committee on Taxonomy of Viruses: progress and prospects - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max L. Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2017)

Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2016) - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2016)